2017
DOI: 10.1021/acs.orglett.7b01103
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed C–H Trifluoroethoxylation of N-Sulfonylbenzamides

Abstract: The trifluoroethyl aryl ethers are important motifs in drug molecules. However, a report devoted specifically to the study of transition-metal-catalyzed C-H trifluoroethoxylation has not been reported to date. A protocol of Pd(II)-catalyzed o-C-H trifluoroethoxylation of a broad range of benzoic acid derivatives (i.e., N-sulfonylbenzamides) has been developed. This method is also applied to the formal synthesis of the drug molecule flecainide, wherein the first m-C-H trifluoroethoxylation is also exemplified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 104 publications
0
35
0
1
Order By: Relevance
“…Also, reactions using some of the difluorocarbene sources require either special reaction apparatus, elevated temperatures, or strong bases. To alleviate some of these limitations and establish milder reaction conditions, visible‐light photoredox catalysis has been used for the generation of the difluorocarbene intermediate . More recently, Ngai et al.…”
Section: Synthesis Of Difluoromethoxylated Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, reactions using some of the difluorocarbene sources require either special reaction apparatus, elevated temperatures, or strong bases. To alleviate some of these limitations and establish milder reaction conditions, visible‐light photoredox catalysis has been used for the generation of the difluorocarbene intermediate . More recently, Ngai et al.…”
Section: Synthesis Of Difluoromethoxylated Compoundsmentioning
confidence: 99%
“…In 2017, Fu and co‐workers reported a strategy that enabled preparation of aromatic difluoromethyl ethers under visible‐light photocatalytic conditions (Scheme ) . The difluorocarbene species, :CF 2 , was generated in situ from commercially available and easy‐to‐handle difluorobromoacetic acid (BrCF 2 CO 2 H) in the presence of fac ‐Ir(ppy) 3 at room temperature upon irradiation with visible light.…”
Section: Synthesis Of Difluoromethoxylated Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under a similar context, the secondary amine‐catalyzed [2+2+2] annulation reaction of nitroolefins 2 , aldehydes 1 , and N ‐protected‐isatin ketamines 102 to the synthesis of spiro‐oxindole piperidine derivatives via an organocatalytic Michael‐aza‐Henry‐hemiaminalization cascade reaction was disclosed by our group in 2017 (Scheme ) . The reaction parameters were systematically screened, and conducting the reaction in MeCN at 40 °C with DBU as base was found to yield excellent results.…”
Section: Asymmetric Catalysis With Chiral Aminementioning
confidence: 99%
“…The commercially available bromodifluoroacetic acid (BrCF 2 CO 2 H, CAS number: 354‐08‐5) was employed in the difluoromethylation of phenols and thiophenols ( 222 ) under visible light with a 23 W CFL . Screening of photocatalysts, bases, and solvents showed that the combination of fac ‐Ir(III)(ppy) 3 , Cs 2 CO 3 , and DMF, respectively, was appropriate for the efficiency of difluoromethylation process (Scheme ).…”
Section: General Introductionmentioning
confidence: 99%